Synthesis and Characterization of Oxide Catalysts Supported on Activated Carbon - Hadi, B. A; Muhammad, A. U; Umar, M. T (Indonesian Scientific Publication, 2025)
The rising costs of conventional hydrotreating catalysts necessitate sustainable alternatives. Here, activated carbon derived from Empty Fruit Bunch (EFB) fibre, a byproduct of palm oil production, was developed as a renewable catalyst support. Using nickel nitrate, cobalt nitrate, and ammonium molybdate as both activating agents and precursors. NiO/C, CoO/C, and MoO₃/C catalysts were synthesized via in-situ activation. SEM/EDX analysis confirmed uniform metal oxide dispersion and revealed porous carbon structures. The results establish EFB-derived activated carbon as a low-cost catalysts support material with significant potential for catalytic upgrading of pyrolysis oil. Its high surface area and tunable properties further enhance its suitability for hydrotreating and other sustainable catalytic applications. This work introduces an in-situ route where metal precursors act as both activators and catalysts precursors, producing efficient EFB-derived catalyst supports for pyrolysis oil upgrading.